A pesquisa em ensino de ciências na educação de pessoas jovens e adultas em artigos científicos de periódicos brasileiros (Qualis A) publicados em 2020 - Freire, Maria Júlia (Universidade Federal de São Carlos, 2021)
The panorama of knowledge produced on the Teaching of Natural Sciences (Biology, Physics, Geology and Chemistry) in Youth and Adult Education (YAE) evidenced a certain scarcity of investigations with analyses of research published in journals specific to the area of Science Teaching. Knowing this gap, the author investigated in a Scientific Initiation (SI) the perspectives of research on Science Teaching in YAE in scientific articles from Qualis A Brazilian journals, in the period from 1979 to 2019. It is understood that scientific knowledge is indispensable to today's human being and that it is constantly developing, so it is worth expanding the Scientific Initiation investigation in articles about Science Teaching in YAE published in 2020. The general objective of this research was to perform a comparative analysis of the perspectives for conceiving the relationship of Science Teaching in YAE identified in the period 1979-2019 with the period 2020, in Qualis A Science Teaching journals in the Brazilian context, in order to attribute greater consistency to the SI results. For this, we took dialogical learning as a reference, because it (a) provides validity for the development of an education that guarantees maximum levels of learning for everyone, (b) to have been conceived by Ramón Flecha in 1997 starting from the modality of Youth and Adult Education in the context of the information society, and (c) to be apparently in line with Scientific Literacy, which perceives scientific knowledge as indispensable to today's human being in view of the challenges of modern society. To do so, the same method of the SI was applied, of bibliographic research, through the exploration of the (14) Brazilian journals of Science Teaching Qualis A in the evaluation of the quadrennium 2013-2016, in which it was searched for articles that researched the intersection between Science Teaching and YAE. For the qualitative analysis of the results it was also adopted the Textual Discourse Analysis that consists of the processes of unitarization, categorization and communication, having as final product of the analysis a metatext. As for the perspectives obtained in qualitative analysis, for the (a) conceptions of learning the categories found in SI and that remain are objectivist and dialectic, and the dialogic category emerges; (b) for Science Teaching perspectives remain the category of social function of science teaching and subcategory of scientific literacy, emerging as a subcategory of curriculum approach the curriculum in action. The results corroborate (a) a lack regarding the amount of research published in the Qualis A Science Teaching journals investigating the Science Teaching -YAE intersection, and (b) the deficit in fulfilling the reparative, equalizing and permanent functions of YAE, as established by the National Education Council, since the learning conceptions used do not consider such aspects in their foundations.
Research on science teaching in youth and adult education in scientific articles from brazilian journals (Qualis A) in 2020
Keywords: EJA; Pesquisa bibliográfica; Aprendizagem dialógica; Alfabetização científica; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO